Enhanced Adsorption of Methyl Orange from Aqueous Phase Using Chitosan–Palmer Amaranth Biochar Composite Microspheres - Guiling Chen; Yitong Yin; Xianting Zhang; Andong Qian; Xiaoyang Pan; Fei Liu; Rui Li (Molecules, 2024)
To develop valuable applications for the invasive weed Palmer amaranth, we utilized it as a novel biochar source and explored its potential for methyl orange adsorption through the synthesis of chitosan-encapsulated Palmer amaranth biochar composite microspheres. Firstly, the prepared microspheres were characterized by scanning electron microscopy and Fourier transform infrared spectroscopy and were demonstrated to have a surface area of 19.6 m2/g, a total pore volume of 0.0664 cm3/g and an average pore diameter of 10.6 nm. Then, the influences of pH, dosage and salt type and concentration on the adsorption efficiency were systematically investigated alongside the adsorption kinetics, isotherms, and thermodynamics. The results reveal that the highest adsorption capacity of methyl orange was obtained at pH 4.0. The adsorption process was well fitted by a pseudo-second-order kinetic model and the Langmuir isotherm model, and was spontaneous and endothermic. Through the Langmuir model, the maximal adsorption capacities of methyl orange were calculated as 495.0, 537.1 and 554.3 mg/g at 25.0, 35.0 and 45.0 °C, respectively. Subsequently, the adsorption mechanisms were elucidated by Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy investigations. It is indicated that electrostatic interactions, hydrogen bonding, π–π interactions and hydrophobic interactions between methyl orange and the composite microspheres were pivotal for the adsorption process. Finally, the regeneration studies demonstrated that after five adsorption–desorption cycles, the microspheres still maintained 93.6% of their initial adsorption capacity for methyl orange. This work not only presents a promising method for mitigating methyl orange pollution but also offers a sustainable approach to managing Palmer amaranth invasion.